2020
DOI: 10.3389/fnagi.2020.582525
|View full text |Cite
|
Sign up to set email alerts
|

Have I Been Here? Sense of Location in People With Alzheimer's Disease

Abstract: Background: When navigating in a particular space, a sense of being at a current location is of great help for the navigators in reaching their destination or getting back to the start. To accomplish this work, interwoven neural structures and neurons are called into play. This system is called the heading direction cell-place cell-grid cell circuit. Evidence from various neuroscience studies has revealed that the regions responsible for this circuit are damaged in the early stages of Alzheimer's disease (AD).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 51 publications
1
11
1
Order By: Relevance
“…Indeed, previous studies have shown severe impairments in scene recognition, remembering turns at decision points and recalling the temporal order of routes in both patients with AD dementia and MCI. Furthermore, some of these studies have found that route continuation and route ordering are impaired in both patients with AD dementia and MCI, to the same extent [11,14,24,27,29,33,42,61,77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous studies have shown severe impairments in scene recognition, remembering turns at decision points and recalling the temporal order of routes in both patients with AD dementia and MCI. Furthermore, some of these studies have found that route continuation and route ordering are impaired in both patients with AD dementia and MCI, to the same extent [11,14,24,27,29,33,42,61,77].…”
Section: Discussionmentioning
confidence: 99%
“…However, these small-scale spatial tests are highly inflexible, measure only a single aspect in the spatial memory spectrum or have proven to be poor predictors of navigational abilities [21] and cognitive decline [22]. Other studies have aimed to simulate the complexity of real-life situations by assessing large-scale spatial navigation in real-world scenarios such as hospital settings (for example, [11,14,[23][24][25][26][27][28]) or with innovative tests incorporating advanced virtual reality (VR) paradigms such as the Memory Island Test and the Sea Hero Quest [14,25,26,[29][30][31][32][33][34][35][36][37][38]. Multiple studies have proven that real-world scenarios and VR applications appear to be more sensitive in identifying spatial navigation deficits in patients with AD in both the prodromal and symptomatic stage [11,14,25,26,[39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion criteria for a diagnosis of prAD were as follows: (1) SPECT showed decreased perfusion in parietal association area, posterior cingulate, precuneus; (2) magnetic resonance imaging (MRI) showed atrophy, especially in the medial temporal lobe and/or posterior cortical regions; (3) objective evidence of impairment in one or more cognitive domains, including memory, attention, language, visuospatial skills, or executive function; (4) independent activities of daily living; (5) other conditions that may cause cognitive impairment must be ruled out (17)(18)(19). The inclusion criteria for the diagnosis of prDLB were as follows: (1) more than one core symptoms of DLB, such as fluctuating cognition, visual hallucinations, rapid eye movement sleep behavior disorder (RBD), and more than one symptom of Parkinson's disease; (2) using TRODAT to confirm the reduced uptake of dopamine transporter in striatum; (3) independent activities of daily living; (4) other conditions that may cause cognitive impairment must be ruled out (20,21).…”
Section: Participantsmentioning
confidence: 99%
“… 33 , 36 A recent study also showed that self-reported spatial navigation abilities may not predict objectively measured sense of location in the real world in individuals with aMCI and mild AD dementia. 37 In addition, the extent of life-space mobility (i.e., the measure of movement extending from within one’s own home to movement beyond one’s own town or geographic region 38 may interfere with reported spatial navigation abilities, as more frequent travel to more remote locations is more challenging. 38 , 39 Although previous studies have suggested potential benefits and limitations of reported spatial navigation abilities in screening for AD, comparisons between self- and informant-reported spatial navigation questionnaires, and their associations with brain atrophy and biomarkers across the AD continuum have not been researched.…”
Section: Introductionmentioning
confidence: 99%